2010
DOI: 10.1002/elps.201000333
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis for analysis of microheterogeneous glutelin subunits in rice (Oryza sativa L.)

Abstract: Glutelin, the major storage protein of rice seed, consists of microheterogenous subunits and partially exists in a macromolecular form that is polymerized by intersubunit disulfide bonds. In order to analyze the glutelin subunits using high-throughput CE, we first identified a sample preparation procedure suitable for CE. The polymerized glutelin treated with a reductant could not dissociate into its constituent monomer subunits when it was dissolved in an acidic solution. However, the glutelin dissociated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…For example, our previous analysis on some glutelin subunit mutants using capillary electrophoresis, a technique suitable for accurate quantification, has demonstrated that mutants Type1, Type2, Type3, and a-123less, in which GluB4, GluA2, GluA1, and their three subunits are deleted, respectively, had apparently no other changes in protein composition and total protein content, suggesting the deletions were compensated evenly by other storage proteins (Katsube-Tanaka et al, 2010).…”
Section: Compensation and Degradation In Glutelin And Globulin Mutantsmentioning
confidence: 99%
“…For example, our previous analysis on some glutelin subunit mutants using capillary electrophoresis, a technique suitable for accurate quantification, has demonstrated that mutants Type1, Type2, Type3, and a-123less, in which GluB4, GluA2, GluA1, and their three subunits are deleted, respectively, had apparently no other changes in protein composition and total protein content, suggesting the deletions were compensated evenly by other storage proteins (Katsube-Tanaka et al, 2010).…”
Section: Compensation and Degradation In Glutelin And Globulin Mutantsmentioning
confidence: 99%
“…Glutelin polypeptide is cleaved into an N-terminal half (acidic subunit) and a C-terminal half (basic subunit) in the vacuole by an aspartic protease (Wang et al 2009 ; Kumamaru et al 2010 ). They are conjugated intra-molecularly and inter-molecularly by disulfide bonds to form a higher structural conformation (Katsube-Tanaka et al 2004 , 2010 ; Kawagoe et al 2005 ; Motoyama et al 2009 ), and they accumulate with α-globulin in PSVs. Glutelin is encoded by a multigene family, and the molecular type has been studied by many researchers before the whole rice genome was revealed (Takaiwa et al 1987 , 1991 ; Masumura et al 1989 ; Takaiwa and Oono 1991 ; Mitsukawa et al 1998 ; Qu et al 2002 ; Kusaba et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we could only speculate about the IgEbinding capacity of the protein encoded by locus Os02gO453600, because both spots 111 and 112 were mixed with the already known IgE-binding proteins, glutelin type-A 1 or glutelin type-B 1, respectively. 40 Glutelin type-B 1 was also identified in the separated spot 113. Spots 114, 115, and 116 corresponded to a 19 kDa globulin, the seed allergenic protein RAG2, and a protein encoded by the gene locus Os07g0216700, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 95%